The Impact of Children’s Programming Education on the Development of Children’s Cognitive Abilities - Xinsheng Liang (Research and Advances in Education, 2024)
This paper delves into the impact of children’s programming education on the development of children’s cognitive abilities. It begins by discussing the rise and development of children’s programming education and the importance of cognitive abilities in the growth of children. It then analyzes in detail the characteristics and advantages of children’s programming education, including teaching methods, teaching tools, and specific ways of cultivating children’s cognitive abilities. Through empirical research, experiments were designed, and data were collected and analyzed to verify the positive impact of children’s programming education on the development of children’s cognitive abilities. At the same time, in response to the challenges faced by children’s programming education, such as the shortage of teachers and the irrationality of curriculum settings, corresponding strategies have been proposed. Finally, the paper summarizes the significance of children’s programming education in the development of children’s cognitive abilities, emphasizes the necessity of further promoting and improving children’s programming education, and looks forward to its future development trends.